Successful tocilizumab treatment for rapidly progressive interstitial lung disease with anti-MDA5-positive juvenile dermatomyositis: a case report and literature review - Qiu, Lingzhi; Shao, Xiaoyan; Ma, Le; Fan, Zhidan; Yu, Haiguo (Frontiers in Pediatrics, 2024)
Background Currently, no established integrated treatment regimen exists for anti-melanoma differentiation-associated gene 5 (anti-MDA5)-positive juvenile dermatomyositis (JDM) complicated by rapidly progressive interstitial lung disease (RP-ILD). We present a case of refractory anti-MDA5-positive JDM with RP-ILD that was successfully treated using a combination of tocilizumab and plasma exchange, along with a review of the relevant literature. Methods A literature review was conducted to gain insights into the clinical features and treatment strategies for managing refractory anti-MDA5-positive JDM complicated by RP-ILD. Results We report a case of successful management of anti-MDA5-positive JDM complicated by RP-ILD using a combination of immunosuppressive agents, plasma exchange, and tocilizumab. Conclusion Tocilizumab may serve as an effective adjunctive treatment option for patients with refractory anti-MDA5-positive JDM complicated by RP-ILD who do not respond to conventional intensive immunosuppressive therapies.